All Days 2010
DOI: 10.2118/135360-ms
|View full text |Cite
|
Sign up to set email alerts
|

Changing the Shape of Fracturing: New Proppant Improves Fracture Conductivity

Abstract: Hydraulic fracturing is used extensively to increase hydrocarbon production from oil and gas formations. Hydraulic fracture conductivity is a key parameter in optimizing the productivity of a well after the fracture treatment. The American Petroleum Institute (API) proppant permeability / fracture conductivity testing results are frequently used in industry fracturing models when selecting the proppant that provides the optimum fracture conductivity for a well's particular reservoir properties. This design met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 47 publications
(13 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…A unique consolidated proppant pack can be created due to the cylindrical shape which can resist the proppant flowback. Another added advantage is the mobility increase of a high-viscosity slurry, which can help in quick fracture cleanup due to higher available permeability (Cheremisin et al 2011;Jia et al 2019;Li et al 2015;McDaniel et al 2010;Osiptsov 2017;Schlumberger 2013Schlumberger , 2015Soetikno et al 2014). The field tests indicated that the friction pressure for rodshaped proppants was 492 psi/1000 ft, significantly lower than 543 psi/1000 ft for spherical particles for an equivalent volume of particles in the slurry.…”
Section: Rod-shaped Proppantsmentioning
confidence: 99%
See 2 more Smart Citations
“…A unique consolidated proppant pack can be created due to the cylindrical shape which can resist the proppant flowback. Another added advantage is the mobility increase of a high-viscosity slurry, which can help in quick fracture cleanup due to higher available permeability (Cheremisin et al 2011;Jia et al 2019;Li et al 2015;McDaniel et al 2010;Osiptsov 2017;Schlumberger 2013Schlumberger , 2015Soetikno et al 2014). The field tests indicated that the friction pressure for rodshaped proppants was 492 psi/1000 ft, significantly lower than 543 psi/1000 ft for spherical particles for an equivalent volume of particles in the slurry.…”
Section: Rod-shaped Proppantsmentioning
confidence: 99%
“…During the settling phase until fracture closure, the fracture conductivity can be reduced if the proppants settle perpendicular to the flow direction. However, multiple slot flow and proppant settling tests revealed that the proppant alignment after settling was completely random (McDaniel et al 2010). Moreover, the proppant diameter should be chosen according to the fracture aperture to avoid any entry restrictions in the fracture.…”
Section: Rod-shaped Proppantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with spherical proppant packs, the elongated proppant packs also demonstrated the advantage of reducing the friction pressure. When elongated shaped materials align in a fluid flow, they can help minimize the turbulent effects that can help to reduce losses due to friction 32 (see Figure 3).…”
Section: Preparation For the Field Tests Of Surface Refracturingmentioning
confidence: 99%
“…For enhanced energy recovery, elongated proppant has already been implemented successfully in many field tests. McDaniel et al 32 reported the first field implementation, proving the possibility of using elongated particles as proppant. The channel fracturing technology with rod‐shaped proppant has been conducted and achieved good performance in a lot of field tests around the world 33‐35 .…”
Section: Introductionmentioning
confidence: 99%